Our experience in the restorative treatment of patients with consequences of the elbow joint injuries - Azizov, Mirkhakim; Togayev, Tokhir (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article deals with results of restorative treatment with use of an electromechanical device in 27 patients at the age of 14-60 years with consequences of injuries in their elbow joints. Good results were achieved in 88.9 % of patients and satisfactory ones in 11.1 % of cases.